The effect of light/dark cycles on performance and welfare in broiler - Ozkan, Murat; Simsek, Ulku Gulcihan (Walter de Gruyter Gmbh, 2022)
The purpose of this study was to compare a continuous lighting programme (23 hours of lighting (L) / 1 hour of darkness (D)) with intermittent lighting programmes (16L: 8D) and also to investigate the effects of the length of the dark cycle in the intermittent programme on the performance, carcass characteristics, water consumption, uniformity, metabolic parameters, and ammonia burns of chickens. Thus, five hundred Ross-308 male chicks were used. The 23L:1D was applied to the chicks for 7 days. On day 7, they were divided into four groups by balancing their live weight; group I: continuous 23L: 1D; group II: intermittent 4x (4L: 2D); group III: intermittent 2x (8L: 4D); group IV: continuous 16L: 8D. The study took place between days 7 and 42. At the end of the study, 10 chickens from each group were slaughtered, their carcass, blood, and bone properties were analysed. Body temperatures and ammonia burns were assessed for all broiler chickens. The mean live weight of group IV was the lowest. The difference among the groups in terms of live weight gains, feed intakes, feed conversion ratios, and survival rates was non-significant. Long-period darkness in group IV significantly dropped the water consumption. On day 21, group III's best uniformity was calculated; but on day 42, the difference was non-significant. The highest breast ratio and the lowest wing ratio beloged to chicks in group I. Their free T-4, glucose, and uric acid levels were lower; whilst their testosterone levels were higher. Body temperature and tibia ash levels were similar across all of the groups. The intermittent lighting programmes increased the number of ammonia burns. Consequently, the long-term darkness negatively affected both the chickens' performance and well-being.
Keywords: broiler; lighting programme; production; hormone; ammonia burns